2019
DOI: 10.5539/elt.v12n6p146
|View full text |Cite
|
Sign up to set email alerts
|

A Sage on a Stage, to Express and Impress: TED Talks for Improving Oral Presentation Skills, Vocabulary Retention and Its Impact on Reducing Speaking Anxiety in ESP Settings

Abstract: This study explores the impact of using TED Talks on improving oral presentation skills of Business English students and vocabulary uptake/retention. It also assesses the impact of improving such hard cognitive skills on increasing Business majors’ speaking anxiety level. Sequential explanatory mixed method was used, which includes both quantitative and qualitative data collection and analyses. Business students’ oral presentation skills were assessed through Oral Presentation Skills Sheet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 62 publications
3
21
0
Order By: Relevance
“…Therefore, TED Talks is one of the ICT tools that can be effectively used to promote speaking skills. It represents an effective instructional tool for developing language skills due to its authentic nature (Salem, 2019).…”
Section: Downloadmentioning
confidence: 99%
“…Therefore, TED Talks is one of the ICT tools that can be effectively used to promote speaking skills. It represents an effective instructional tool for developing language skills due to its authentic nature (Salem, 2019).…”
Section: Downloadmentioning
confidence: 99%
“…However, only two studies were found on using TED talks for teaching Business English (Ramejkis, n.d.;Salem, 2019). Both of them explored the impact of using TED Talks on improving oral presentation skills of Business English students.…”
Section: Ted Talks As a Teaching Toolmentioning
confidence: 99%
“…Both of them explored the impact of using TED Talks on improving oral presentation skills of Business English students. It was revealed that Business majors in the experimental group are more enthusiastic, energetic and motivated as they became more confident and free of anxiety and tension (Salem, 2019).…”
Section: Ted Talks As a Teaching Toolmentioning
confidence: 99%
“…Numerous professions such as Economy and Business, Health, Politics, and Diplomacy recognised the influence of polished presentation skills as a necessity for a successful career (Ciarocco, 2018). They use presentations for business results discussions, developing strategies, pitching ideas, debating about their opinions, but the impact of the presented depends on the speakers' oral presentation skills (Salem, 2019). Academic researchers acknowledge presentation skills as the most important skills for employment, even in comparison to intelligence, moreover, they point out that poor presentation skills could impede the individual's career (Lent, 2018).…”
Section: Introductionmentioning
confidence: 99%